Sugarcane Water Stress Tolerance Mechanisms and Its Implications on Developing Biotechnology Solutions - Ferreira, Thais H. S.; Tsunada, Max S.; Bassi, Denis; Araújo, Pedro; Mattiello, Lucia; Guidelli, Giovanna V.; Righetto, Germanna L.; Gonçalves, Vanessa R.; Lakshmanan, Prakash; Menossi, Marcelo (Frontiers in Plant Science, 2017)
Sugarcane is a unique crop with the ability to accumulate high levels of sugar and is a commercially viable source of biomass for bioelectricity and second-generation bioethanol. Water deficit is the single largest abiotic stress affecting sugarcane productivity and the development of water use efficient and drought tolerant cultivars is an imperative for all major sugarcane producing countries.. This review summarizes the physiological and molecular studies on water deficit stress in sugarcane, with the aim to help formulate more effective research strategies for advancing our knowledge on genes and mechanisms underpinning plant response to water stress. We also overview transgenic studies in sugarcane, with an emphasis on the potential strategies to develop superior sugarcane varieties that improve crop productivity in drought-prone environments.